An assessment of market recovery strategies to boost sales: a case study of Zimpapers - Chikwena, Stanley (Midlands State University, 2015)
The research ought to assess the market recovery strategies to boost sales by Zimpapersl.t.d. these are the strategies that were adopted by Zimpapers after feeling the market share which was decreasing at an increasing rate covering the period as from 2012-2014. The major sources used were Kotler, P (2001), Sudarsanam, S. and Lai, J. (2001, and Schoenberg,RCollierN and Bowman,C (2013). A descriptive research design was adopted on a sample of 80 respondents in the following apportionment 40 questionnaires to Zimpapers personnel, 25 to clients and 15 to sales-rep vendors were an 82.5% response rate was attained, Rubin (2009) postulated that an adequate research analysis should be at least 40%, a 60% is considered good whilst a 70% and above is regarded excellent hence in this instance the response rate was valid up to required standard. A quantitative research was adopted as it numeric in nature it is then easy to come up with comparative conclusions which are easy to understand and follow up the trends. Also 3 interviews were scheduled and attained a 100% response rate as all the scheduled interviews were successfully conducted. More focus was on the Zimpapers personnel as they were the one actually feeling the heat of the market share they were losing to rival firms. Simple graphs, pie charts and at most tables were used to present the data gathered from the respondents so as to make it very easy to interpret the information gathered. Having all this relevant information about the market recovery strategies, the researcher then concluded that some adopted strategies such as acquiring new machinery was actually a cost increasing activity hence the company should focus mainly on strategies which respondents recommended the most such as going online as it proved to be of outmost great importance, this is then gave the company the opportunity to target international market.